2022
DOI: 10.25259/sni_456_2022
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of dropped head syndrome: A systematic review

Abstract: Background: Dropped head syndrome (DHS) is uncommon and involves severe weakness of neck-extensor muscles resulting in a progressive reducible cervical kyphosis. The first-line management consists of medical treatment targeted at diagnosing underlying pathologies. However, the surgical management of DHS has not been well studied. Methods: Here, we systematically reviewed the PubMed and Cochrane databases for DHS using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. All re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Therefore, surgical intervention can be applied when conservative treatment fails [ 10 ]. However, the requirement for extensive realignment of the cervical spine is associated with a high rate of complications [ 1 ]. Kurakawa et al reported that correction and posterior fixation of cervical kyphosis may cause a high percentage having postoperative complications such as C5 nerve palsy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, surgical intervention can be applied when conservative treatment fails [ 10 ]. However, the requirement for extensive realignment of the cervical spine is associated with a high rate of complications [ 1 ]. Kurakawa et al reported that correction and posterior fixation of cervical kyphosis may cause a high percentage having postoperative complications such as C5 nerve palsy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of postoperative dysphagia or airway-related complications after surgery for DHS were reported to be related to anterior procedure, not the alignment change [ 1 ]. However, realignment was certainly related to the dysphagia in our patient because immediate relief of the symptoms occurred after downgrading surgery which decreased the cervical lordosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous reports, IDHS patients show abnormal posture during standing and walking [ 3 , 4 ], have a slower gait than healthy subjects [ 3 ], and the severity of horizontal gaze disorder is associated with the patient’s gait speed [ 5 ]. Furthermore, while there have been reports on surgical treatment [ 6 ] and rehabilitation [ 7 ] for the treatment of IDHS, no effective treatment modality has been established. However, some case series and interventional studies reported that IDHS symptoms improved due to programs that include lower extremity or whole-body exercises [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%